Identification And Diversity Of Crab In Pondang And Lopana Beach Waters, South Minahasa - Lepa, Bryan Gabriel; Paransa, Darus Saadah J; Mantiri, Desy M. H; Boneka, Farnis B; Lumoindong, Frans; Tilaar, Ferdinand F. (Sam Ratulangi University, 2022)
There are crab species that live in the forest and supratidal areas, on sandy, rocky, and muddy coastal areas. The aim of this research is to identify the morphology, of meristic crabs and the effect of the moon phase on species diversity. Sampling locations were on the coast of Pondang Village and Lopana Village, sampling using the roaming method and carried out at the two lowest low tide phases during the dead moon and full moon phases, during the lowest low tide crabs were generally found with walking legs. Based on the identification of the morphology of crabs found on the coast of Pondang Village and Lopana Village, East Amurang District, South Minahasa Regency, there are six species of them Ocypode ceratophthalmus (Stimpson, 1858), Grapsus albolineatus (Latreille in Milbert, 1892), Eriphia sebana (Shaw and Nodder, 1803), Atergatis floridus (Linnaeus, 1767), Pilumnus vespertilio (Fabricius, 1793), Episesarma mederi (Edwards, 1853). Keywords: Coastal; Habitat; Crabs; Morphology; meristic AbstrakTerdapat jenis kepiting yang hidup di daerah hutan dan supratidal, di daerah pesisir pantai berpasir, berbatu dan berlumpur. Tujuan penelitian mengidentifikasi secara morfologi, meristik kepiting dan pengaruh fase bulan terhadap keanekaragaman spesies. Lokasi pengambilan sampel di pesisir pantai Kelurahan Pondang dan Desa Lopana, pengambilan sampel menggunakan metode jelajah serta dilakukan pada dua fase surut terendah saat fase bulan mati dan purnama, saat surut terendah umumnya dijumpai kepiting yang memiliki kaki jalan. Berdasarkan identifikasi morfologi kepiting yang ditemukan di pesisir pantai Kelurahan Pondang dan Desa Lopana, Kecamatan Amurang Timur, Kabupaten Minahasa Selatan, terdapat enam spesies antaranya Ocypode ceratophthalmus (Stimpson, 1858), Grapsus albolineatus (Latreille dalam Milbert,1892), Eriphia sebana (Shaw dan Nodder, 1803), Atergatis floridus (Linnaeus, 1767), Pilumnus vespertilio (Fabricius, 1793), Episesarma mederi (Edwards, 1853). Kata Kunci : Pesisir; Habitat; Kepiting; Morfologi; Meristik